Foreign objects? Web content management systems, journalistic cultures and the ontology of software. (January 2015) - Rodgers, Scott
Research on 'digital' journalism has focused largely on online news, with comparatively less interest in the longer-term implications of software and computational technologies. Drawing upon a 6-year study of the Toronto Star, this article provides an account of TOPS, an in-house web content management system which served as the backbone ofthestar.com for 6 years. For some, TOPS was a successful software innovation, while for others, a strategic digital 'property'. But for most journalists, it was slow, deficient in functionality, aesthetically unappealing and cumbersome. Although several organizational factors can explain TOPS' obstinacy, I argue for particular attention to the complex ontology of software. Based on an outline of this ontology, I suggest software be taken seriously as an object of journalism, which implies acknowledging its partial autonomy from human use or authorization, accounting for its ability to mutate indefinitely and analysing its capacity to encourage forms of 'computational thinking'.